Analysis of The Mathematical Thinking Levels of Individual and Team Athletes in Terms of Different Variables - TEKİN, Nedim; KEPCEOĞLU, İbrahim; İPEKOĞLU, Aysun; BÜLBÜL, Alpay (Bilge Akademi, 2021)
This study was carried out to examine athletes' mathematical thinking levels who do individual and team sports in different variables. The study was conducted with a relational screening model, which is one of the general screening models. The data were collected by a survey method. "Mathematical Thinking Scale" was used to determine the mathematical thinking levels of athletes. The research population was composed of licensed athletes studying in high schools and universities in the 2020-2021 academic year in Turkey, while 459 licensed athletes determined among these students by a simple random method made up the sample group. The Independent-Samples T-Test was applied to determine the differences between the participants' gender, education and branch variables, and their mathematical thinking level. The Pearson Correlation test was applied to determine the relationship between age, sports year, and mathematical thinking levels. As a result of the analysis, a significant difference was observed favouring female participants in the gender variable and mathematical thinking skills sub-dimension. Additionally, it was determined that there was a significant positive relationship between the sports year and the reasoning sub-dimension. As a result, it is thought that the more inclusion of individual or team sports types in education programs will contribute to an individual's mathematics and academic success.
Keywords: Alan Eğitimleri; team athletes; Individual athletes; team athletes; mathematical thinking; mathematical thinking; Other Fields of Education; Individual athletes; 4. Education; 10. No inequality